Elemental Analysis of Commonly Consumed Rice in Nigeria using PIXE Technique - Usikalu, M. R.; PrzybyÅ‚owicz, W. J.; Mtshali, C.; Babarimisa, I. O. (Journal of Informatics and Mathematical Sciences, 2017)
This study investigated the essential element (P, Cl, K, Ca, Mn, Fe, Cu and Zn) concentra-tions of some local and imported rice commonly consumed in Nigeria. This is done in order to select the rice with high nutrient to combat malnutrition, especially in children. Proton-induced X-ray emission (PIXE) techniques available at iThemba Labs Someset West, South Africa was used for the analysis. The elemental concentration obtained for Ofada are \(8805.5\boldsymbol{±}221\), \(276.5\boldsymbol{±}32\), \(3704.5\boldsymbol{±}39\), \(212$\boldsymbol{±}8\), \(110.5\boldsymbol{±}8\), \(125.5\boldsymbol{±}7\), \(14.5\boldsymbol{±}1\) and \(44.5\boldsymbol{±}4\) ppm, while for the imported rice we got \(2862.5\boldsymbol{±}150\), \(399\boldsymbol{±}22\), \(1433\boldsymbol{±}28\), \(4.15\boldsymbol{±}2\), \(8.4\boldsymbol{±}0.8\), \(4.75\boldsymbol{±}1\) and \(9.5\boldsymbol{±}2\) ppm for P, Cl, K, Ca, Mn, Fe, Cu and Zn respectively. Phosporus (P) has the highest elemental concentration in all samples. Ofada, one of the local rice was found to have the highest elemental concentration while pure imported rice had the lowest concentrations of the elements. The study suggests that consumption of locally-cultivated (Ofada) rice should be encouraged in order to reduce malnutrition in children in Nigeria.